Kewenangan Pemerintah Kota Kupang dalam Meningkatkan Kesejahteraan Anak Jalanan di Kota Kupang - Laura Angelin Tanur Djari; Hernimus Ratu Udju; Megi O. Radji (Pusat Riset dan Inovasi Nasional, 2025)
Street Children are one of the complex social problems in big cities in Indonesia The Kupang City Government has issued a policy through Kupang City Regional Regulation No. 8 of 2013 which regulates the Handling and Empowerment of Street Children, Vagrants, and Beggars in its area. The Social Service has not been fully effective in supporting social welfare. This can be seen from the problem of Street Children in Kupang City, where there are still many underage children who are often seen wandering the streets. They are involved in various activities, such as selling newspapers, snacks, and even begging to anyone who stops. The type of research used in this study uses empirical legal research where this research method functions to see the law in a real sense and examine how the law works in the community. The results of the research and discussion show that (1) the results of the research conducted at the Kupang City Social Service are related to the Duties and Responsibilities of the Social Service in providing social welfare services for street children. This refers to the Kupang City Regional Regulation Number 8 of 2013 concerning the Handling and Empowerment of Street Children. As the implementer, the Social Service has the authority to provide guidance and control to street children. In addition, the implementing agents involved also carry out their duties and functions in accordance with their roles as regional apparatus, ensuring that the coaching process runs in accordance with the responsibilities carried out. (2) Factors that hinder the city social services in providing services in the field of social welfare for street children in Kupang City include internal factors.